PENGARUH CURRENT RATIO (CR) DAN DEBT TO EQUITY RATIO (DER) TERHADAP PERUBAHAN LABA PADA PERUSAHAAN SUB SEKTOR FARMASI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Dini Susmiandini; Ismi Yolanda Wirawan (Universitas La Tansa Mashiro, 2017)
This study aims to determine the effect of Current Ratio and Debt to Equity Ratio on changes in earnings, measure the condition of the company and find out how much influence the position of Current Ratio and Debt to Equity Ratios significantly on changes in earnings.The method used is descriptive method with a case study approach and uses secondary data. The population used is a pharmaceutical sub-sector company in manufacturing companies listed on the Indonesia Stock Exchange as many as 10 companies and the sample is 6 companies.Based on the results of testing that has been done the results of the t test show that Current Ratiot does not have a significant effect on earnings changes where thitung <ttable (-0.885 <2.052) and its significance value (0.401> 0.05) means that H0 is acceptable and H1 is rejected. While Debt to Equity Ratio t count (-0.715 <2.052) and its significance value (0.481> 0.05) which means that Debt to Equity Ratio does not significantly influence earnings changes and this means that H0 is accepted and H2 is rejected. And based on the test results f, Fcount> Ftable (0.365 <3.34) and the significance value of 0.698> 0.05 means that H0 can be accepted, so it can be concluded that simultaneous Current variable Ratiodan Debt to Equity Ratio does not have a significant effect on changes in earnings and this means that H0 is accepted and H3 is rejected. Based on the results and data analysis, the minimum value, maximum value and average value for each company are obtained. The management must be able to improve good financial performance, especially to increase Current Ratio, Debt to Equity Ratio and changes in earnings because this is the most important assessment for investors to invest their funds in the company, the better financial performance, the better to convince investors to invest funds.